PENGARUH KOMITMEN ORGANISASI DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI DESA BALUNG LOR - Nita Herlina; Maheni Ika Sari; Achmad Hasan Hafidzi (Growth, 2021)
This study aims to analyze the effect of organizational commitment and communication on employee performance in Balung Lor Village. The population in this study were all employees of Balung Lor Village, totaling 30 people and the head of the RW Balung Lor Village as many as 13 people so that the total population was 43 people. The sampling method in this study is a saturated sampling technique or census, so that the total population is a total sample of 43 employees. The data used in this study are primary data and secondary data. The data analysis method used in this study is multiple linear regression analysis using SPSS version 20.00 software. The results of this study indicate that organizational commitment and communication have a significant effect on employee performance.